Assessment of the microbial load of airway clearance devices used by a cohort of children with cystic fibrosis. Issue 3 (September 2021) - Linnane, B.; O'Connell, N.H.; Obande, E.; Dunne, S.S.; Clancy, C.; Kiernan, M.G.; McGrath, D.; O'Sullivan, K.J.; O'Sullivan, L.; Dunne, C.P.
Summary: Background: Positive expiratory pressure (PEP) devices are an important element of the management of cystic fibrosis, and of other respiratory diseases. Whereas there have been reports in the literature of contamination of airway clearance devices and their surfaces by microbial pathogens, there is little evidence available regarding such contamination and its contribution to respiratory infection. Aim: To establish whether pathogenic bacteria can contaminate PEP devices in the context of normal cleaning and maintenance practices. Methods: Patients' home-use clearance devices were brought to a routine clinic appointment and collected for microbiology sampling and analysis. The patients were provided with replacement devices. Nineteen such devices were collected from 17 patients, reflecting use of multiple devices by some patients. Swabs were taken and cultured from each patient's used device, the patient's airway, as well as from new unopened and unused devices that acted as controls. Results: Seven of 19 devices (37%) tested positive for presence of pathogenic bacteria. Device-cleaning methods varied among patients and non-sterilization methods were found to be ineffective at removing pathogens. Microbial species found on the devices did not correlate with those identified from airway swabs. Conclusion: This study demonstrates the presence of pathogens on positive expiratory pressure devices. The potential for transmission of these pathogens to the patient's airway and the risk of infection remains unclear and requires further study.